The Urgence Of Islamic Philosophy For Education In Elementary School - Siti Nurhalisa; Anika Musayadah; Naila Ulfatusy Syarifah; Adila Puspitasari; Nasikhin Nasikhin; Mahfud Junaedi (JASNA : Journal For Aswaja Studies, 2022)
AbstractThe growing opinion that philosophy is a teaching that is prohibited in Islam often has a negative impact on education, especially for basic education. This study aims to determine the role of Islamic educational philosophyfor  Islamic  basic  education.  This  study  uses  the  literature  study  method  to  find  information related  to  the  theme  of  Islamic philosophy  as  a  science  at the basic  education  level.  From the  results  of the analysis that has been carried out, research data shows that the importance of Islamic philosophy for basic  education  in  three  roles  is  the  reason;  First,  the  philosophy  of  Islamic  education  plays  a  role  in compiling  thinking  activities  to  find  the  concept  of  basic  education  in  overcoming  various  problems  of Islamic  education  through  the  study  of  the  Qur'an  and  Hadith.  Second,  the  philosophy  of  Islamic education  leads  basic  education  teachers  to  develop  critical  thinking  on  material  objects  and  formal objects. Material objects include all existing realities (forms), while formal objects are closely related to human  nature  from  the  point  of  view  of  basic  Islamic  education.  This  role  is  carried  out  through  the method  of  selection,  search,  discussion,  and  a  comprehensive  approach  to  the  study  of  Islamic  basic education  philosophy.  This  research  contributes  to  the  development  of  education  so  that  it  is  not  anti-philosophical.Keywords: Philosophy, Islam, Elementary Schools.AbstrakOpini   yang   berkembang   bahwa   filsafat   merupakan   ajaran   yang   dilarang  dalam   Islam   acapkali memberikan   dampak   buruk   terhadap   pendidikan,  khusunya   jenjang   pendidikan   dasar. Kajian   ini bertujuan  untuk  mengetahui  peranan  filsafat  pendidikan  Islam  bagi  pendidikan  dasar  Islam.  Penelitian ini menggunakan metode studi pustaka untuk menggali informasi terkait tema filsafat islam sebagai ilmu pada  jenjang  pendidikan  dasar.  Dari  hasil  analisis  yang  telah  dilakukan  diperoleh data  penelitian yang menunjukkan  bahwapentingnya  filsafat  Islam  bagi  pendidikan  dasar  didasarkan  pada  tiga peran  yang menjadi alasan;  pertama,  filsafat  pendidikan  islam berperan  dalam  menyusun  aktivias  berpikir  untuk menemukan  konsep  pendidikan  dasar  dalam  mengatasi  berbagai  problem  pendidikan  Islam  melalui kajian  al-Qur'an  dan  Hadist.  Kedua, filsafat  pendidikan  islam  menggiring  guru  pendidikan  dasar  untuk menyusun  pemikiran  kritis  atas  objek  materiil  dan  objek  formal.  Objek  materi  meliputi  segala  realitas yang  ada  (wujud),  sedangkan  objek  formal  berhubungan  erat  dengan  hakikat  manusia  dari  sudut pandang  pendidikan  dasar Islam.  Peranan  ini    terlaksana  melalui  metode  pemilihan,  pencarian, pembahasan,    dan    pendekatan    studi    filsafat    pendidikan    dasar Islam    yang    dilakukan    secara komprehensif.Penelitian  ini  memberikan  kontribusi  bagi  perkembangan  pendidikan  agar  tidak  bersifat anti-filsafat.Kata Kunci: Filsafat, Islam, Pendidikan Dasar